Ex-situ micro X-ray computed tomography tests and image-based simulation of UHPFRC beams under bending - Zhang, X; Yang, Z; Pang, M; Yao, Y; Li, QM; Marrow, TJ (Elsevier, 2021)
Micro-structures of fibre reinforced composites play a pivotal role in their damage, fracture and failure mechanisms. This study first carried out ex-situ micro X-ray Computed Tomography (μXCT) tests of three small ultra-high-performance fibre reinforced concrete (UHPFRC) beams under progressive three-point bending. The first two beams were continuously loaded until failure and their central regions with the main flexural crack were scanned by μXCT before and after the test. The third beam was subjected to five cycles of loading-unloading until failure, and was scanned by μXCT after each unloading. The 3D μXCT images with 30 μm voxel resolution were then processed and analysed, and the spatial distribution, number, orientation and dimension of pores and fibres were statistically quantified. The micro-scale failure mechanisms, such as fibre bridging of cracks, fibre-matrix interfacial slipping and debonding, and matrix failure, were visualised and analysed. The μXCT images of the first two beams were then segmented and directly converted to meso-scale finite element models based on orientation-dependent bond-slip relations for the fibre-matrix interfaces and continuum damage plasticity for the matrix. The simulated load-displacement curves, fracture processes and final crack morphologies were found in excellent agreement with the tests. It was also found that the position, dimension and orientation of fibres and pores have significant effects on the damage and fracture initiation and evolution from both the tests and the simulations.